A Brief Analysis of the Correlation Between Budget and Performance in Romanian Soccer - COCIOC, Paul (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
Starting from the widely held idea in Romanian football (and not only) that a higher budget is almost the only requirement for better performance for a club, our study investigates the existence and intensity of such a correlation. At the same time, we sought to deepen the correlations within club expenditures, through those related to the player roster as an expression of its value, where we expect a to see a higher intensity in relation to sports results. Due to data availability considerations, the analysis is limited to the latest seasons of the domestic championship. The approach is based on rank correlation, and the tools used are Kendall’s coefficient and Spearman’s coefficient. The results obtained confirm expectations regarding the existence of a direct relationship between the amounts spent by a club and its position in the rankings, but the intensity of this correlation is significantly lower than expected, at least at the level of total expenditures. Article history: Received 2025 August 18; Revised 2025 September 30; Accepted 2025 October 09;Available online 2025 November 20; Available print 2025 November 30